Evaluation of gingival and periodontal status in obese and non-obese type II diabetic patients – a cross sectional study - SriChinthu, Kenniayan Kumar; Pavithra, Velusamy; Kumar, G.S.; Prasad, Harikrishnan; Prema, Perumal; Yoithapprabhunath, Thuckanickenpalayam Ragunathan; Rangarajan, Nagarajan (Medicine and Pharmacy Reports, 2020)
Objective. The aim of this study was to evaluate gingival and periodontal status in obese and non-obese type II Diabetic Patients. Methods. The study population comprised of 75 subjects visiting the outpatient department of our institution, divided into three different groups, group 1 (obese diabetic), group 2 (non-obese diabetic), and group 3 (obese, non-diabetic). Diabetic status was assessed with HbA1c values and obesity status was assessed by body mass index (BMI) score greater than or equal to 30 kg/m2. Gingival and periodontal status were assessed using the Gingival Index (GI) and Community Periodontal Index (CPI) respectively. Results. The mean gingival index score in group 1, group 2, and group 3 were 1.58, 1.54, and 1.25, respectively. Gingival status was poor among obese and non-obese diabetic subjects [Groups 1 & 2] when compared with obese non-diabetic patients [Group – 3]. The periodontal status showed that periodontal pockets were increased in diabetic obese group (15.4%), followed by diabetic non obese (4.66%), and non-diabetic obese (2%) group respectively and loss of attachment was severe in diabetic obese group (60.7%), followed by diabetic non obese (45.9%) and non-diabetic obese (15.3%) respectively. Conclusion. Gingival and periodontal status was poor in the obese diabetic group compared to non-obese diabetic and obese non diabetic group. Hence, the risk of gingivitis and periodontitis in obese diabetic patients should be addressed earlier to prevent further complications and achieve a good oral health status.